(untitled) (Web of Humanities: Journal of Social Science and Humanitarian Research, 2024)
Each learner may face u number of problems while learning foreign languages. One of them is speaking skills problem, which is common among many learners. Currently, in the world of globalization, fluency in foreign languages plays an important role. Many employers when considering candidates for the position prefer people who speak at least one foreign language. Thus, the article is devoted to the peculiarities of the application of the communicative method of teaching foreign languages. The main ideas of communicative linguistics defining the communicative method are summarized. The principles on which the communicative approach to teaching foreign languages is based are considered.